Sunscreens: UV filters to protect us: Part 1: Changing regulations and choices for optimal sun protection - Nina Sabzevari, DO; Sultan Qiblawi, MBA, M3; Scott A. Norton, MD, MPH, MSc; David Fivenson, MD (Wolters Kluwer, 2021)
Sunscreens are topical preparations containing any number of ultraviolet filters (UVFs). The first part of the review will focus on the recent Food and Drug Administration (FDA) regulations of 2019 and general use of these agents. While sunscreen products are becoming more regulated in the United States, we still lag behind other countries in our options for UVFs. Sun protection to prevent skin cancer and aging changes should be a combination of sun avoidance, protective structures, and clothing as well as use of sunscreen products. Newer and safer products are needed to help supplement and replace older agents as well as improve their cosmetic acceptability. This will be a review of ingredients, local toxicities (i.e. contact dermatitis, photocontact dermatitis), special considerations for children, and cosmesis of sunscreen preparations. Part 2 will focus on the environmental, ecological and human toxicities that have been increasingly related to UVFs.